Comparison of Growth Rate of Male Buffalo Calves under Open Grazing and Stall Feeding System - Afzal, M.; Anwar, M.; Mirza, M.A.; Andrabi, S.M.H. (Pakistan Journal of Nutrition, 2009)
This study was conducted to compare the effect of open grazing system and feeding green fodder at the stall (cut and carry system) on the growth of male buffalo calves. Twelve male buffalo calves (of Nili Ravi breed) were either grazed (n = 5) on natural pasture or were offered seasonal green fodder ad lib in the manger (n = 7). The calves were kept on these treatments for 9 months. Live body weight of the calves was recorded at the start of trial and then fortnightly. The overall weight gain per day over nine months of feeding period did not differ significantly between open grazing (0.415±0.028kg) and stall fed groups (0.433±0.056kg) (P > 0.05). It is concluded that grazing on natural pasture may result in growth of male buffalo calves comparable to that after feeding them cultivated green fodder at the manger.